Aspects of Poultry Manure Low-Emission Utilization Process - Malovanyy, Myroslav; Odnorih, Zoriana; Kanda, Mariia; Parashchiienko, Iryna (International Journal of Engineering and Technology, 2018)
The article provides the results of study of an impact of poultry manure combined with a mixture of clinoptilolite and palygorskite on condition of the agricultural lands. It outlines changes in the concentration of ammonia nitrogen and phosphorus, calcium, potassium, and magnesium in soils. Also, it shows the prospects of use of the proposed composition for the purpose of utilization of poultry manure. Â Â